54.0k views
4 votes
I need help to simplify 3x (x² - x - 2) + 2x (3 - x) - 7x. I've tried to solve the problem three times and have gotten 2x² - 2x - 6, then, x² - 1x - 6, then, 3x³ - 5x² - 13x, I can't figure out what I'm doing wrong.

1 Answer

3 votes

Given the initial expression,


3x(x^2-x-2)+2x(3-x)-7x

Simplify it as shown below


\begin{gathered} =3x*x^2-3x*x-3x*2+2x*3-2x*x-7x \\ =3x^3-3x^2-6x+6x-2x^2-7x \end{gathered}
\begin{gathered} =3x^3-3x^2-2x^2-7x \\ =3x^3-5x^2-7x \end{gathered}

Thus, the answer is 3x^3-5x^2-7x

User GAMELASTER
by
5.3k points